Human Fetal Liver: An In Vitro Model of Erythropoiesis - Guillaume Pourcher; Christelle Mazurier; Yé Yong King; Marie-Catherine Giarratana; Ladan Kobari; Daniela Boehm; Luc Douay; Hélène Lapillonne (Hindawi Limited, 2011)
We previously described the large-scale production of RBCs from hematopoietic stem cells (HSCs) of diverse sources. Our present efforts are focused to produce RBCs thanks to an unlimited source of stem cells. Human embryonic stem (ES) cells or induced pluripotent stem cell (iPS) are the natural candidates. Even if the proof of RBCs production from these sources has been done, their amplification ability is to date not sufficient for a transfusion application. In this work, our protocol of RBC production was applied to HSC isolated from fetal liver (FL) as an intermediate source between embryonic and adult stem cells. We studied the erythroid potential of FL-derived CD34+ cells. In this in vitro model, maturation that is enucleation reaches a lower level compared to adult sources as observed for embryonic or iP, but, interestingly, they (i) displayed a dramatic in vitro expansion (100-fold more when compared to CB CD34+) and (ii) 100% cloning efficiency in hematopoietic progenitor assays after 3 days of erythroid induction, as compared to 10-15% cloning efficiency for adult CD34+ cells. This work supports the idea that FL remains a model of study and is not a candidate for ex vivo RBCS production for blood transfusion as a direct source of stem cells but could be helpful to understand and enhance proliferation abilities for primitive cells such as ES cells or iPS.